Optimization of the Performance of the Criminal Research Unit in Handling Online Fraud Criminal Acts to Improve Case Settlement in the Jurisdiction of the Madiun City Police - Maha Putra, I Nyoman Andika; Kusuma, Alif Bryan Pradana; Boseke, Timothy Torro Ignatius Paskah (Tanggon Kosala, 2024)
The creation of public security and order must be based on the condition of the community that gets legal certainty. Still, in fact, in the jurisdiction of the Madiun City Police, many cases of online fraud are not accompanied by optimal handling by the Madiun City Police Criminal Investigation Unit. The purpose of this writing is to find out how the performance of investigators in handling cases and find solutions to the factors causing the low number of online fraud case resolutions in the jurisdiction of the Madiun City Police. This writing uses a qualitative approach with observation data collection techniques, documentation studies, and interviews. By using performance theory and SWOT analysis, the author found that in the process of resolving online fraud cases, there were still zero because investigators had difficulty finding the perpetrator's position and the lack of technological facilities that could support the implementation of tasks, besides that there were also inhibiting factors in handling the resolution of online fraud cases, starting from an inadequate budget and members never carrying out Specialist Development Education (Dikbangspes) related to cybercrime. Based on the author's findings, the performance of the Madiun City Police Criminal Investigation Unit in handling online fraud cases to improve case resolution was less than optimal. It is recommended that members of this unit undergo special training in cybercrime and acquire special equipment for information technology and handling of electronic evidence to increase the resolution rate of online fraud cases.